Early Cardiac Allograft Vasculopathy: Are the Viruses to Blame?. (2012) - Aggarwal, Ashim; Pyle, Joseph; Hamilton, John; Bhat, Geetha
Abstract : This paper describes a case of early (7 months after transplant) cardiac allograft vasculopathy. This-43-year-old (CMV positive, EBV negative) female patient underwent an orthotopic heart transplant with a (CMV negative, EBV positive) donor heart. She had a history of herpes zoster infection and postherpetic neuralgia in the past. The patient's panel reactive antibodies had been almost undetectable on routine surveillance testing, and her surveillance endomyocardial biopsies apart from a few episodes of mild-to-moderate acute cellular rejection (treated adequately with steroids) never showed any evidence of humoral rejection. The postoperative course was complicated by multiple admissions for upper respiratory symptoms, and the patient tested positive for entero, rhino, and coronaviruses serologies. During her last admission (seven months postoperatively) the patient developed mild left ventricular dysfunction with an ejection fraction of 40%. The patient's endomyocardial biopsy done at that time revealed concentric intimal proliferation and inflammation resulting in near-total luminal occlusion in the epicardial and the intramyocardial coronary vessels, suggestive of graft vasculopathy with no evidence of rejection, and the patient had a fatal ventricular arrhythmia.